The Physical Development And Clinical Course Of Celiac Disease In Children Depending On Adherence To Diet Therapy - Turakulov B.Kx.; Turakulova K.H. (International Journal of Medical Sciences And Clinical Research, 2025)
To assess the clinical features of the typical form of celiac disease and the physical development of children depending on adherence to a gluten-free diet.